Contrasting aerosol optical and radiative properties between dust and urban haze episodes in megacities of Pakistan. (January 2018) - Iftikhar, Muhammad; Alam, Khan; Sorooshian, Armin; Syed, Waqar Adil; Bibi, Samina; Bibi, Humera
Abstract: Satellite and ground based remote sensors provide vital information about aerosol optical and radiative properties. Analysis of aerosol optical and radiative properties during heavy aerosol loading events in Pakistan are limited and, therefore, require in-depth examination. This work examines aerosol properties and radiative forcing during Dust Episodes (DE) and Haze Episodes (HE) between 2010 and 2014 over mega cities of Pakistan (Karachi and Lahore). Episodes having the daily averaged values of Aerosol Optical Depth (AOD) exceeding 1 were selected. DE were associated with high AOD and low Ångström Exponent (AE) over Karachi and Lahore while high AOD and high AE values were associated with HE over Lahore. Aerosol volume size distributions (AVSD) exhibited a bimodal lognormal distribution with a noticeable coarse mode peak at a radius of 2.24 μ m during DE, whereas a fine mode peak was prominent at a radius 0.25 μ m during HE. The results reveal distinct differences between HE and DE for spectral profiles of several parameters including Single Scattering Albedo (SSA), ASYmmetry parameter (ASY), and the real and imaginary components of refractive index (RRI and IRI). The AOD-AE correlation revealed that dust was the dominant aerosol type during DE and that biomass burning and urban/industrial aerosol types were pronounced during HE. Aerosol radiative forcing (ARF) was estimated using the Santa Barbra DISORT Atmospheric Radiative Transfer (SBDART) model. Calculations revealed a negative ARF at the Top Of the Atmosphere (ARFTOA ) and at the Bottom Of the Atmosphere (ARFBOA ), with positive ARF within the Atmosphere (ARFATM ) during both DE and HE over Karachi and Lahore. Furthermore, estimations of ARFATM by SBDART were shown to be in good agreement with values derived from AERONET data for DE and HE over Karachi and Lahore. Highlights: Ground and satellite-based evidence of large aerosol loading in Pakistan. Dust episodes show high AOD & low AE, represent the presence of coarse particles. Haze episodes show high AOD & high AE, represent the presence of fine particles. Both dust and haze produced significant heating of the atmosphere.